Soil quality and yield attributes of soybean on an Ultisol conditioned using cogongrass biochar enriched with nitrogen fertilizer dissolved in seaweed extract - Kilowasid, Muhammad Harjoni; Cahyani, Imas Nur; Febrianti; Aldi, Muhammad; Rahni, Nini Mila; Alam, Syamsu; Suaib; Wijayanto, Teguh; Hasid, Rachmawati; Boer, Dirvamena; Madiki, Abdul; Hadini, Hamirul; Arief, Norma; Muhidin; Nurmas, Andi; Arma, Makmur Jaya; Nuraida, Wa Ode (Brawijaya University, 2025)
The soil quality of Ultisol, which is indicated by its chemical properties, arbuscular mycorrhizal fungi (AMF), and root nodules, is important for soybean growth. Cogongrass biochar enriched with N fertilizer solution using solvent from seaweed extract can change the soil quality. Using various seaweed extract solvents, this study sought to (i) test the impact of cogongrass biochar enriched with N fertilizer solution on the soil chemical quality and (ii) examine the effects of soil chemical changes on AMF, root nodules, tissue nutrient content, and soybean yield. The treatments consisted of (i) without biochar (B0), (ii) cogongrass biochar without enrichment (BN0), (iii) cogongrass biochar enriched with urea solution using solvent from extract of Kappapychus alvarezii (BNK), (iv) cogongrass biochar enriched with urea solution using solvent from extract of Sargassum sp. (BNS), and (v) cogongrass biochar enriched with urea solution using solvent extract of Ulva lactuca (BNU). In a randomized block design, each treatment was carried out three times. With or without fertilization, cogongrass biochar improves the chemical fertility of the soil. The increase in NH4+-N and nitrate-N content of the soil in enriched cogongrass biochar was greater than in unenriched. The AMF spores density and root nodules were reduced following enrichment. When biochar was added, there were more pods, pod dry weight, total seeds, and regular seeds per plant. In conclusion, the impact of increasing soil ammonium content led to decreased density of AMF spores, root infections, and root nodules. The level of available P greatly affected the components of soybean yield in Ultisol.